Transvesicoscopic Bipolar Sealing of Vesicovaginal Fistula - Akkoç, Ali (J Endourol Case Rep, 2018)
Introduction: Vesicovaginal fistula (VVF) is a problem that physically and psychologically debilitates the patient. Options for treatment of VVF include transabdominal, transvaginal, transvesical, laparoscopic, and robotic repair or minimally invasive methods such as fulguration. We describe a novel minimally invasive technique: transvesicoscopic bipolar sealing of the vesicovaginal fistula (TBSF). Case Presentation: We carried out the transvesicoscopic sealing of VVF with 5 mm of diameter on a 46-year-old woman, who had a failed conservative treatment with a Foley catheter placement. The patient was informed about the modified surgical procedure before operation. The fistula tract was sealed by using an electrothermal bipolar vessel sealer through a 5-mm transvesical ports. The patient was discharged on the first postoperative day and was on anticholinergic medications after the operation. The patient remained dry after the removal of the catheter at the third postoperative week. Conclusion: In select cases of VVF, TBSF may be effectively used for closure of the fistula tract.